Effects of Nalbuphine on Gastrointestinal Function in Post-Operative Critical Ill Patients Admitted to the ICU: A Multicenter Randomized Controlled Trial - Yan, Yun; Lei, Chong; Su, Binxiao; Dong, Enxia; Wang, Guangming; Li, Bin; Li, Xinyu; Li, Aiguang; Gan, Guifen; Chen, Yu; Zhang, Xijing (Frontiers in Medicine, 2022)
Background Gastrointestinal (GI) function can be a significant problem in critically ill patients and is associated with detrimental outcomes. The administration of opioids for pain reduction is thought to contribute to GI dysfunction. We tested whether nalbuphine, a mixed agonist/antagonist opioid modulator, can promote GI recovery in postoperative critical patients admitted to the intensive care unit (ICU) and compared it with fentanyl, a selective mu opioid receptor (MOR) agonist. Methods This is a multicenter, single-blind, randomized controlled trial to investigate whether nalbuphine improves the GI recovery in ICU patients after surgery, and compared it with fentanyl. The primary outcome was the time to first defecation. Secondary outcomes included the use of sedatives, enemas or laxatives, the acute gastrointestinal injury (AGI) grade, the incidence of vomiting, and the lengths of ICU and hospital stays. Results We randomized 436 patients, and a total of 369 patients were included in the modified intention-to-treat population (mITT) (185 to the nalbuphine group and 184 to the fentanyl group). The baseline demographic characteristics of the two groups were comparable after randomization. There was no significant difference in the time to defecation between the two groups [hazard ratio (HR) 0.94, 95% CI 0.74–1.19, p = 0.62]. There was no significant difference in the secondary outcomes between the two groups. Conclusion We found no evidence that nalbuphine administration can improve the GI function in postoperative critical patients admitted to the ICU compared with fentanyl. However, the CI was wide and we could not exclude the clinically important difference.